Polydactylus luparensis, a new species of threadfin (Perciformes: Polynemidae) from the Batang Lupar River, Sarawak, Borneo, Malaysia - Lim, Pek Khiok Annie; Motomura, Hiroyuki; Gambang, Albert Chuan (Zootaxa, 2010)
A new species of large-sized brackishwater threadfin, Polydactylus luparensis, is described from the Batang Lupar River in Sarawak, Malaysia, Borneo on the basis of 5 specimens (610–715 mm standard length). The new species can be distinguished from all other Polydactylus by having 8 dorsal-fin spines, first spine tiny, second spine very strong (its width more than 5 times the width of remaining spines); 13 second dorsal-fin soft rays; 11 anal-fin soft rays; 12 pectoralfin rays, its length 22–24% (mean 23%) of SL, posterior tip not reaching a vertical through posterior tip of depressed pelvic fin; 6 pectoral filaments, fourth or fifth filament longest, its length 77–85% (mean 81%) of SL, posterior tip extending slightly beyond caudal-fin base; pored lateral-lined scales 67–75 (mean 71); lateral line unbranched, extending onto upper end of lower caudal-fin lobe; 6 scale rows above lateral line, 8 below; 14 gill rakers on upper limb, 18 on lower limb, 32 in total; occipital profile concave; posterior margin of maxilla extending considerably beyond a vertical through posterior margin of adipose eyelid; depth of posterior margin of maxilla 4–5% (mean 5%) of SL, greater than orbit diameter; well-developed swimbladder present; basal half of third to sixth pectoral filament white, becoming black distally. Polydactylus luparensis is currently known only from the mouth of the Batang Lupar River.